X. couchianus and X. hellerii genome models provide genomic variation insight among Xiphophorus species. (December 2016) - Shen, Yingjia; Chalopin, Domitille; Garcia, Tzintzuni; Boswell, Mikki; Boswell, William; Shiryev, Sergey; Agarwala, Richa; Volff, Jean-Nicolas; Postlethwait, John; Schartl, Manfred; Minx, Patrick; Warren, Wesley; et al.
Abstract Background Xiphophorus fishes are represented by 26 live-bearing species of tropical fish that express many attributes (e.g., viviparity, genetic and phenotypic variation, ecological adaptation, varied sexual developmental mechanisms, ability to produce fertile interspecies hybrids) that have made attractive research models for over 85 years. Use of various interspecies hybrids to investigate the genetics underlying spontaneous and induced tumorigenesis has resulted in the development and maintenance of pedigreedXiphophorus lines specifically bred for research. The recent availability of theX. maculatus reference genome assembly now provides unprecedented opportunities for novel and exciting comparative research studies amongXiphophorus species. Results We present sequencing, assembly and annotation of two new genomes representingXiphophorus couchianus andXiphophorus hellerii . The finalX. couchianus andX. hellerii assemblies have total sizes of 708 Mb and 734 Mb and correspond to 98 % and 102 % of theX. maculatus Jp 163 A genome size, respectively. The rates of single nucleotide change range from 1 per 52 bp to 1 per 69 bp among the three genomes and the impact of putatively damaging variants are presented. In addition, a survey of transposable elements allowed us to deduce an ancestral TE landscape, uncovered potential active TEs and document a recent burst of TEs during evolution of this genus. Conclusions Two newXiphophorus genomes and their corresponding transcriptomes were efficiently assembled, the former using a novel guided assembly approach. Three assembled genome sequences within this single vertebrate order of new world live-bearing fishes will accelerate our understanding of relationship between environmental adaptation and genome evolution. In addition, these genome resources provide capability to determine allele specific gene regulation among interspecies hybrids produced by crossing any of the three species that are known to produce progeny predisposed to tumor development.